Integrated Supply Chain Management Model of Small-Scale Organic Farming Businesses - Agustine Eva Maria Soekesi; Veronica Kusdiartini; Jonathan Billy Alfasen (Journal of Management and Business Environment (JMBE), 2026)
This study aims to evaluate Prayogi's small-scale business experiencing profit stagnancy using a comprehensive business management approach from the aspects of operations, marketing, human resources, and finance. The study of the operational aspect includes the development of products and operating systems, the marketing aspect includes the concept of the marketing mix. The human resource aspect includes the concept of motivation to achieve business performance, and the financial aspect includes the charging of costs and investment feasibility. This qualitative research with primary and secondary qualitative and quantitative data uses a recruitment method in the form of in-depth interviews and observations as well as documentation studies. The business development efforts that have been implemented are studied using a comprehensive approach from all these aspects with the triangulation method and investment feasibility for financial data. This study with a comprehensive management approach is expected to provide analysis results in the form of a design business management model to be used in order to optimize business potential and overcome business obstacles that have been perceived by business actors. With organic agricultural land management through integrated outlets, it can optimize the entire process from land cultivation to processing and distribution of finished products to consumers. This model is able to improve the financial performance of farmer partners who have only been able to process but do not have access and market network to distribute their crops.